Study guides

Q: How do you factor 6x squared plus 3x equals 0?

Write your answer...

Submit

Related questions

(3x - y+ 2)(3x + y + 2)

It is: 3x*(x+7)

(3x + 1)(x + 5)

(x + 5)(3x + 1)

3(x2 + 3x + 1)

(3x + 3y)(x + y) = 3(x + y)2

If that's -18y2, the answer is (3x - 2y)(x + 9y)

(6x + t)(3x + t)

(3x - 2)(x + 8)

6xyz(3x + 2y + z)

(x - 1)(3x + 5)

(3x - 1)(x + 2)

3x2 + 10x + 3 = (x + 3)(3x + 1).

It is: 3x2+6x-11 = 0

It is a quadratic equation.

y = 3x + 21x2 = 3x(1 + 7x)

It is: x(x+3)

3x2+10x+7 = (3x+7)(x+1) when factored

k = 0.1

(x + 2)(x + 1)

3x 2 + 2x - 5 = (x - 1)(3x + 5).

3x2 + x = x*(3x + 1)

Yes.

20x2 - 3x + 10 does not have any real factors.

(x + 3)(3x - 2)